ON STABILITY OF THE OIL DISPLACEMENT FRONT UNDER CONDITIONS OF THERMOGAS IMPACT ON THE OIL BEARING LAYER - K. V. Dobrego (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The method of thermogas impact on the oil bearing layer is a perspective one to improve oil recovery. It is now under experimental implementation in Belarus. Stability of the thermal front and that of the oil displacement is a point of principle for the given technology. The article offers solution based on the method of small perturbations for the problem of the oil-displacement front stability under thermogas impact on the oil layer. The perturbation growth increment is shown to be quite different from that of the gas filtration combustion. Being determined by the perturbation wave number (or wave length), by difference in speed of the blowing filtration and that of the heat development front, by the ratios of densities, filtration coefficients, compressibility of the displacement agent and the displaced oil mass, and by other parameters. The author analyses the main parameters influencing the stability of the front. Recommendations are given on possible methods and procedures improving stability of the displacement front (neutralizing perturbation growth). The mechanisms of suppression or compensation of the front perturbation growth are as follows: the crude oil viscosity reduction and increase of that of the displacement agent, the displacement agent compressibility increase, increase of the thermogas impact heat-front width in the first instance at the expense of the temperature growth and alteration in the chemism (low temperature catalysts utilization, etc.), reduction in speed of the front propagation and/or correspondingly of the displacement agent feed. Utilization of the gas or water-gas displacement agent as well as the agent impregnation with hydrophobic gases provides a relatively better stability of the front as compared to that employing water based compounds. Analytical data and derived recommendations are offered for utilization within the framework of general techniques and procedures of the thermogas impact process management in the context of developmental and experimental-industrial oil extraction. Further research into methods and mechanisms of the displacement front perturbation compensation, including the front dynamics at nonlinear stage, might be conducted via detailed 2D and 3D numerical simulation of the system.